Peran Bimbingan dan Konseling Dalam Menangani Konflik Interpersonal di Lingkungan Masyarakat - Adela, Nurul; Syukur, Yarmis; T, Taufik (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Interpersonal conflicts are a common phenomenon in social interactions, arising due to differences in perspectives, values, personal interests, or social needs. In increasingly dynamic societies, these conflicts can disrupt harmony, reduce solidarity, and even threaten social stability. If not properly managed, conflicts can escalate into more serious issues, including physical altercations and social disintegration. This research explores the role of counseling services in resolving interpersonal conflicts. By utilizing individual counseling, individuals can better understand themselves and others, develop empathy, and establish healthier communication patterns. The study reveals that structured counseling approaches can significantly reduce conflict impacts, improve interpersonal relationships, and foster a more harmonious community. Data collected from various case studies highlights the positive influence of counseling in conflict resolution, demonstrating its potential for creating more inclusive and peaceful social environments.